A version - Wesely, Nicolas D., author; Beachy-Quick, Dan, advisor; Cooperman, Matthew, committee member; Jazz Harvey, Madeline, committee member (Colorado State University. Libraries, 2023)
At surface level "a version" enacts a poetic exploration of form and its myriad influences on creative intent and execution, with particular interest in that mysterious echo of formal play—the sestina. A deeper investigation of the thesis reveals the intricate movement of how poetic self might be realized through the navigation of these various, highly active, literary lineages, which themselves arrive as echoes of past, present, and future writings, experiences, and hopes, here largely circling military history, myth, family, physical body, and love. This thesis exhibits the movement toward, and simultaneously away from, the constraints of form, asking how it is that creativity enters into free flowing abundance through formal parameters; highlighting those moments when repetition deviates from defined meaning and achieves a polyvocality of authorial lineage; a version of a version that has always been and never been before. Here the sestina is pushed into sprawling forays of liturgical praise and negation. It assumes forms and roles meant for other times and spaces, and by so doing, shows its adaptability (and so too our own) toward an immediate presence of modern poetics.
Keywords: poetry; form; sestina